MODEL IDEAL PROMOSI DAN MUTASI APARATUR PERADILAN INDONESIA - Irfan Fachruddin (Jurnal Hukum dan Peradilan, 2012)
Promotion and Implementation of the consequences of mutations causing a correlation between the quality of promotion and transfer to the performance and behavior of judges. Promotions and mutations that do not cause trouble families would improve morale and performance, instead the promotion and transfer of judges to make family life difficult and frustrating declining morale and performance. Then the fight promotion and transfer to the material does not encourage the growth of professionalism of judges and job performance. Hence the need for normative policy governing promotion and transfer mechanisms for the basis implementation equitable promotion and transfer. Compiled promotion and transfer patterns using the system region / territory with the division of the province, the region (some provinces), the national territory. Reclassification of the court by adding criteria case complexity and dynamics of the economy in addition to the substantive elements, circumstances of the case and supporting elements, population, population density, as well as communication and transportation. Imposed purely functional status. Promotion of judges / class civil servants are not hampered by the same leadership position the judge or judges of the lower classes of the judge concerned. It was also necessary to minimize the differences between leaders facility with the judge, so the judge does not have to hunt comfortably leadership positions and perform tasks on its position. Openness is limited, such inspraak and hearing, an opportunity to participate in determining the policy of the authority by a judge that the object of promotion and transfer. Keywords: Promotions and mutations, Justice Reform